The maximum negative power and force modulation during hard and soft landing in alpine skiers - Minetti, A. E.; Susta, D. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: In downhill skiing the mechanical potential energy gained during the ascent is partially lost by snow displacement during curves, but a great deal of energy dissipation is provided by lower limb muscles. Their eccentric contraction has been assessed during maximum damping maneuvers (drop landing) in the past (Minetti et al. 1998). Here we present an extended version of the previous test devoted also to evaluate the ability to manage very soft landings, which could be associated to a lower deceleration on snow.